Sources of perceived social support and cognitive function among older adults: a longitudinal study in rural China - Gui, Shiqi; Wang, Jing; Li, Qiushuo; Chen, Hao; Jiang, Zhiyue; Hu, Jin; Yang, Xing; Yang, Jingyuan (Frontiers in Aging Neuroscience, 2024)
Studies have shown the positive impact of perceived social support on cognitive function among older adults in rural areas. However, existing studies often overlook the impact of different support sources. This study aimed to explore the relationship between the diverse sources of perceived social support and cognitive function. Methods Participants were drawn from the Guizhou Rural Older Adults' Health Study (HSRO) in China. We included 791 participants who participated in a baseline survey in 2019 and a 3-year follow-up survey. Perceived social support was investigated from the six main sources (friend, relative, children, spouse, sibling, and neighbor). Hierarchical linear regression models were used to observe the effects of diverse sources of perceived social support and their combinations on cognitive function.Cognitive function was positively associated with perceived support from children, friends, and neighbors. A positive association was found between cognitive function and increases in each additional source [β = 0.75 (95%CI: 0.51, 0.98), p < 0.001]. Older adults who perceived support from both children and friends showed better cognitive function [β = 2.53 (95%CI: 1.35, 3.72), p < 0.001]. The perception of support from spouse, siblings, and relatives did not show a statistically significant association with cognitive function among older adults in rural areas. A positive association was found between cognitive function and increases in each additional source Conclusions This study found that the association between different sources of perceived social support and